Probabilistic Gas Dispersion Analysis Due to Natural Gas Pipeline Leakage Using ALOHA: A Case Study of Transmission Pipeline from Custody Metering to Tire Plant - Fitra Suharianto; Burniadi Moballa; Anda Iviana Juniani (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Gas leakage in pipeline systems represents a critical hazard in the oil and gas industry, posing significant risks to human safety and the environment. This study aims to perform a probabilistic analysis of natural gas dispersion resulting from pipeline leakage using ALOHA (Areal Locations of Hazardous Atmospheres) integrated with statistical wind data analysis. Meteorological data over 25 years (2000–2024; 219,167 observation hours) were analyzed using Weibull distribution and wind rose methods to characterize the dominant wind regime. The results indicate that low wind speeds (0.5–2.5 m/s) dominate site conditions (77.1%), limiting gas dilution and increasing accumulation near the source. The dominant dispersion direction is identified in the southwest-to-south sector (213.75°–236.25°). Under these conditions, the red zone (≥30,000 ppm, 60% LEL) extends approximately 89.6 m, while in worst-case scenarios it reaches up to 198 m. Vapor Cloud Explosion (VCE) overpressure remains below 1.0 psi. Probabilistic integration of all scenarios produces a consequence probability map identifying high-risk zones along the right-of-way (ROW). These findings support improved risk assessment and provide a basis for targeted mitigation strategies in pipeline safety management.